INTENSIVE METHOD OF RAISING FISH – FACTOR OF HIGH PRODUCTIVITY OF POND FARMS (Scientific journal of the Fergana State University, 2023)
The article highlights the research work on intensive fish farming based on innovative fish farming technology in accordance with the climate of our republic. Cyprinids grown in polyculture in mini-ponds create water circulation with favorable hydrobiological conditions.